Zdrojová analýza financování vybrané investice v obci - Kučera, Patrik (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Tato bakalářská práce s názvem Zdrojová analýza financování vybrané investice v obci je zaměřena na možnosti, kterými lze vybraná investice financovat. Práce je rozdělena na dvě části, na teoretickou a praktickou. Teoretická část definuje a rozděluje investice a dále pak popisuje jednotlivé finanční zdroje, které je možno využít při financování veřejné investice. Praktická část pojednává o možnostech financování konkrétní investice v obci. Vybraná investice je novostavba mateřské školy v městysi Drásov. Cílem této práce je vyhledání a zpracování všech dostupných finančních zdrojů a následně zvolit optimální variantu financování.

This bachelor´s thesis called Source analysis of financing of selected investment in the municipality is focused on possibilities which can be used for financing the selected investment. This work is divided into two parts, theoretical and practical. The theoretical part defines and divides investments and then describes the financial resources that can be used for financing public investment. The practical part discusses the possibilities of financing specific investment in the municipality. The selected investment is a new building of kindergarten in the township of Drásov. The goal of this thesis is to find and elaborate all available financial resources and then to choose the optimal variant of financing.
Source Analysis of Financing of Selected Invesment in the Municipaliti
Keywords: Investice; Financování; Strukturální fondy; Státní fondy; Dotace; Rozpočet; Bankovní úvěry; Obec; Swot analýza; Investment; Financing; Structural Funds; State Funds; Subsidy; Budget; Bank loans; Municipality; Swot analysis